Safety and efficacy of a new octavalent combined Erysipelas, Parvo and Leptospira vaccine in gilts against Leptospira interrogans serovar Pomona associated disease and foetal death. Issue 32 (31st July 2015) - Jacobs, A.A.C.; Harks, F.; Hoeijmakers, M.; Collell, M.; Segers, R.P.A.M.
Abstract The safety and protective efficacy of a new octavalent combination vaccine containing inactivated Erysipelothrix rhusiopathiae, Parvovirus, and Leptospira interrogans (sensu lato) serogroups Canicola, Icterohaemorrhagiae, Australis (Bratislava), Grippotyphosa, Pomona and Tarassovi – Porcilis® Ery + Parvo + Lepto – was evaluated in laboratory studies and under field conditions. The safety (2× overdose and repeated dose) was tested in 26 gilts. In this study, neither vaccine related temperature increase nor other systemic reactions were observed after intramuscular vaccination. No local reactions were observed except for one animal that had a small local reaction (2 cm diameter) that lasted for 5 days after the third vaccination. Efficacy was tested in 40 gilts. A group of 20 gilts was vaccinated at 20 and 24 weeks of age with Porcilis® Ery + Parvo + Lepto and a group of 20 age- and source-matched animals served as the control group. The gilts were inseminated at 41 weeks or 66 weeks of age and were challenged with serovar Pomona 10 weeks after insemination, corresponding to 6 months (n = 2 × 10) and 12 months (n = 2 × 10) after the last vaccination. After both the 6- and 12-month challenges the control animals developed clinical signs (fever, lethargy and anorexia) and leptospiraemia as determined by positive blood culture. In addition, both the 6- and 12-month challenges resulted in death of 21% and 27% of the total number of foetuses in the control groups, respectively. Clinical signs and leptospiraemia were statistically significantly lower in vaccinated gilts after both the 6- and 12-month challenges. In addition, foetal death was statistically significantly lower (3% and 2%, respectively) in vaccinated gilts after both the 6- and 12 month challenges. The vaccine was tested further under field conditions on a Portuguese farm with a history of an increasing abortion rate associated with a Leptospira serovar Pomona infection (confirmed by PCR and serology). This study was designed as an observational-longitudinal field study. At the start of the study, all breeding sows and replacement gilts on the farm were vaccinated twice with Porcilis® Ery + Parvo + Lepto at an interval of 4 weeks. Starting six months after the primary vaccination schedule, the animals were re-vaccinated during the second week of every subsequent lactation. New replacement gilts were vaccinated using the same schedule. After vaccination, the abortion rate reduced rapidly from 12.6% in winter months of 2012 (December 2011 to March 2012) to 0.5% in winter months of 2013, a statistical significant decrease of 96%. The total number of abortions on the farm decreased from 55 in 2012 to 6 in 2013. Thereafter, the abortion rate remained stable and in the period December 2013 to April 2014 was still low (0.6%). In conclusion, the present studies demonstrate that the octavalent Porcilis® Ery + Parvo + Lepto vaccine can be safely used in gilts and sows and induces significant protection, for the duration of at least one year, against serovar Pomona induced clinical signs, leptospiraemia and foetal death. Protection against Pomona associated reproductive failure was confirmed under field conditions where a significant reduction in abortion rate was observed.